Successful minimally invasive management of nonvascular grade IV blunt renal trauma with complete transection in a 7-year-old girl - Zlatan Zvizdic; Emir Milisic; Asmir Jonuzi; Melika Bukvic; Sanela Vesnic; Lejla Milisic; Irmina Sefic Pasic; Semir Vranic (Elsevier, 2022)
Non-operative treatment of high-grade renal trauma in hemodynamically stable children is gaining increasing acceptance nowadays. However, the management of isolated grade IV injuries, particularly those with complete renal fracture and separation of the poles with intact blood supply, is still controversial. Although such injuries have a decreased likelihood of spontaneous resolution, not all require open operative repair. They can be treated with a minimally invasive combination of internal and external drainage. Herein, we report a case of a 7-year-old girl who presented with a nonvascular grade IV blunt renal trauma with a complete renal transection, successfully treated with ureteral stent placement and ultrasound-guided percutaneous drainage of the perinephric urinoma. We also present a brief literature review on this rare lesion in children.